Geospatial variation in dietary patterns and their association with heart disease in Bangladeshi population: Evidence from a nationwide survey - Hassan, Rafid; Ali, Masum; Saha, Sanjib; Akhter, Sadika; Amin, Md. Ruhul (2024)
Heart disease is a significant public health threat, and its burden is increasing worldwide. Recent evidence suggests that dietary pattern is a key modifiable factor for heart disease. Research regarding dietary patterns and heart disease in Bangladesh with their spatial variability is limited. In this study, the spatial variation and relationship between dietary patterns and heart disease among Bangladeshi people was investigated. The country-representative Household Income and Expenditure Survey 2016 dataset was used, and a total of 77,207 participants aged 30 years and over were included. A principal component analysis was conducted to derive the dietary patterns. Both statistical and spatial analyses were performed. The overall prevalence of heart disease was 3.6%, with a variation of 0.6% to 10.4% across districts of Bangladesh. Three major dietary patterns, named “festival pattern”, “pickles and fast foods pattern”, and “rice and vegetable pattern” were identified, accounting for 25.2% of the total dietary variance. Both the dietary pattern and heart disease rate varied across the region. A higher risk of heart disease was persistent in the western-south, southern, central, and eastern regions, as was greater adherence to the “festival pattern” and “pickles and fast foods pattern.” After adjusting for confounders, participants with the highest adherence to the "rice and vegetable pattern" were associated with a lower likelihood of developing heart disease (AOR: 0.78, 95% CI: 0.64–0.95, p <0.05), while the highest adherence to the "pickles and fast foods pattern" was associated with a higher likelihood of developing heart disease (AOR: 1.50, 95% CI: 1.27–1.76, p <0.001). The spatial disparities in the prevalence of heart disease and dietary patterns underscore the significance of prioritizing intervention at the district level, especially in the western-south, southern, central, and eastern regions, to control the rising heart disease trends in Bangladesh.